2008
DOI: 10.1126/science.1164387
|View full text |Cite
|
Sign up to set email alerts
|

Control of Toxic Marine Dinoflagellate Blooms by Serial Parasitic Killers

Abstract: The marine dinoflagellates commonly responsible for toxic red tides are parasitized by other dinoflagellate species. Using culture-independent environmental ribosomal RNA sequences and fluorescence markers, we identified host-specific infections among several species. Each parasitoid produces 60 to 400 offspring, leading to extraordinarily rapid control of the host's population. During 3 consecutive years of observation in a natural estuary, all dinoflagellates observed were chronically infected, and a given h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
273
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(282 citation statements)
references
References 18 publications
6
273
0
Order By: Relevance
“…These flagellates were generally present in low numbers except for station five, where they were abundant (Figure 4). The coverage of the probe Alv01 (Chambouvet et al, 2008) decreased since its publication (Supplementary Table S1), hence the actual numbers were likely higher than reported here. Presence of vermiforms would have confirmed whether this group is indeed parasitic for sea-ice algae.…”
Section: Importance Of Picoeukaryotes In Sea Icementioning
confidence: 53%
“…These flagellates were generally present in low numbers except for station five, where they were abundant (Figure 4). The coverage of the probe Alv01 (Chambouvet et al, 2008) decreased since its publication (Supplementary Table S1), hence the actual numbers were likely higher than reported here. Presence of vermiforms would have confirmed whether this group is indeed parasitic for sea-ice algae.…”
Section: Importance Of Picoeukaryotes In Sea Icementioning
confidence: 53%
“…This alternation between a sporangium-hosted dormant stage and a chemically-activated, free-living virulent stage stands as an efficient strategy for success in the maintenance of the parasitoid population. How do they survive between host blooms, either by serially infecting a sequence of dinoflagellate hosts, as shown for other parasites (Chambouvet et al, 2008), or by sporangia sinking to the sediments along with host cysts and remaining dormant therein until favourable conditions for resuspension and activation occur, remains to be solved.…”
mentioning
confidence: 99%
“…Parasitoids have been identified as a main cause of mortality of harmful dinoflagellates (Taylor, 1968;Chambouvet et al, 2008), to the extent that their deliberate use has been suggested as a biological mitigation of marine harmful algal blooms (Taylor, 1968), in the same manner it is done in agricultural applications on land. The suggestion has faced opposition on the basis of the lack of knowledge on their specificity, the mechanisms of infection and the potential side effects (Anderson, 2009).…”
mentioning
confidence: 99%
“…Viral infection has been shown to control blooms of the coccolithophore Emiliania huxleyi in the Northern Atlantic (Wilson et al 2002), while parasitic protists in the order Syndiniales have been coupled with collapses of blooms of dinoflagellatespeciesintheMediterraneanSea (Chambouvet et al 2008). Increased impact of algal viruses and parasites would decrease the amount of food available for pelagic and benthic grazers.…”
Section: Microbial Processesmentioning
confidence: 99%